Development of the Relationships Among Dynamic Balance Control, Inter-limb Coordination, and Torso Coordination During Gait in Children Aged 3–10 Years - Mani, Hiroki; Miyagishima, Saori; Kozuka, Naoki; Inoue, Takahiro; Hasegawa, Naoya; Asaka, Tadayoshi (Frontiers in Human Neuroscience, 2021)
Knowledge about the developmental process of dynamic balance control comprised of upper arms and upper legs coordination and trunk and pelvis twist coordination is important to advance effective balance assessment for abnormal development. However, the mechanisms of these coordination and balance control during gait in childhood are unknown. This study examined the development of dynamic postural stability, upper arm and upper leg coordination, and trunk and pelvic twist coordination during gait, and investigated the potential mechanisms integrating the central nervous system with inter-limb coordination and trunk and pelvic twist coordination to control extrapolated center of the body mass (XCOM). This study included 77 healthy children aged 3–10 years and 15 young adults. The child cohort was divided into four groups by age: 3–4, 5–6, 7–8, and 9–10 years. Participants walked barefoot at a self-selected walking speed along an 8 m walkway. A motion capture system was used for calculating the XCOM, the spatial margin of stability (MoS), and phase coupling movements of the upper arms, upper legs, trunk, and pelvic segments. MoS in the mediolateral axis was significantly higher in the young adults than in all children groups. Contralateral coordination (ipsilateral upper arm and contralateral upper leg combination) gradually changed to an in-phase pattern with increasing age until age 9. Significant correlations of XCOMML with contralateral coordination and with trunk and pelvic twist coordination (trunk/pelvis coordination) were found. Significant correlations between contralateral coordination and trunk/pelvis coordination were observed only in the 5–6 years and 7–8 years groups. Dynamic postural stability during gait was not fully mature at age 10. XCOM control is associated with the development of contralateral coordination and trunk/pelvis coordination. The closer to in-phase pattern of contralateral upper limb coordination improved the XCOM fluctuations. Conversely, the out-of-phase pattern (about 90 degrees) of the trunk/pelvis coordination increased the XCOM fluctuation. Additionally, a different control strategy was used among children 3–8 years of age and individuals over 9 years of age, which suggests that 3–4-year-old children showed a disorderly coordination strategy between limb swing and torso movement, and in children 5–8 years of age, limb swing depended on trunk/pelvis coordination.